Accounting for friction in the mechanical testing of athletics tracks - Andena, L.; Gobbi, R.; Meda, P.; Zalaffi, S.; Marenghi, A. (Sports Engineering, 2024)
This investigation deals with the problem of identifying the mechanical behaviour of rubbers from compression tests, performed on specimens having unfavorable geometry. A typical situation is that of flat specimens obtained from high-friction sports surfaces. To this purpose, experimental tests were conducted, aimed at measuring friction under various conditions and evaluating its effect on the compressive behavior of different rubber samples. The experimental results have been interpreted in view of an existing analytical model proposed by Gent and coworkers. The method was shown to be valid within a relatively broad range of conditions (in terms of materials, lubrication and aspect ratio). Its application allowed the creation of virtual "frictionless" curves, by rescaling experimental data for the stiffening factor predicted by Gent model. These curves represent more closely the intrinsic material behaviour, removing the large frictional contribution present in the experimental tests, and can be used as a more reliable input for numerical simulations.